Effects of Age and Expertise on Mental Representation of the Throwing Movement Among 6- to 16-Year-Olds - Gromeier, Michael; Schack, Thomas; Koester, Dirk (Frontiers in Psychology, 2022)
The aim of this paper is to assess the development of mental representation of the overhead throw-ing movement as a function of age and expertise. The mental representation structure of the over-head throwing movement was measured using the Structural Dimensional Analysis-Motoric meth-od (SDA-M) that reflects the organization of basic action concepts (BACs). BACs are fundamental building blocks of mental representations which comprise of functional, sensory, spatio-temporal, and biomechanical characteristics of a movement (Schack, 2010). In this study novices and hand-ball athletes (N = 199) were grouped each according to the level of development in motor ontogen-esis (childhood, pubescence, and adolescence). As a result, novices of all age groups showed the same unstructured mental representation. Athletes in the earliest age band resemble all novices’ groups and showed similar unstructured mental representation. Whereas athletes within pubescence and adolescence showed functionally well-structured representations, which were similar to the structure of the reference group (N = 8). These results are consistent with a previous investigation of related quantitative and qualitative performance parameters of the throwing movement (Gromei-er, Koester, & Schack, 2017). Without an increased training, neither the throwing performance nor the associated mental representation is unlikely to improve further by itself or automatically.